Transformasi Digital dan Strategi Nilai Tambah: Pemberdayaan Kelompok Petani Perempuan (KWT) melalui Pemasaran Digital Terpadu dan Inovasi Produk di Desa sumberdem Kecamatan Wonosari - Yudha Pradana; Agung Winarno; Agus Hermawan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Rural women farmers in developing countries often face significant challenges in scaling their businesses due to conventional management practices and limited access to digital markets. In Wonosari Village, the Women Farmers Group (KWT) possessed abundant local resources like coffee and vegetables but suffered from low added value and lack of professional organizational structures. This study aims to evaluate the impact of a comprehensive intervention focusing on digital transformation and value-added strategies to empower the KWT Wonosari toward entrepreneurial independence. A participatory action research (PAR) approach was employed, involving 50 members of KWT Wonosari. The intervention included intensive workshops on product innovation, digital marketing integration via Instagram and TikTok, branding development, and the implementation of standardized financial reporting and operational procedures (SOP). Data were collected through field observations, pre-and post-training assessments, and qualitative interviews. The findings indicate a significant shift in the members' mindset from subsistence farming to a professional entrepreneurial orientation. The program successfully established a formal organizational structure, generated new value-added processed products, and created a robust digital presence with integrated visual branding. Furthermore, the implementation of simple accounting systems enhanced financial transparency and accountability within the group. This study demonstrates that the synergy between academic expertise and community participation is a critical driver for overcoming the digital divide in rural areas. These results contribute to the achievement of Sustainable Development Goal (SDG) 8 by promoting inclusive economic growth and decent work through community-based digital empowerment.